NEW CHUNG-LI METEOR RADAR IN TAIWAN – PRELIMINARY RESULTS - Ching-Lun Su; Po-Hsun Chiu; Ruey-Ming Kuong; Hsyang-Chan Chen; Yen-Hsyang Chu; A. Narendra Babu; P. S. Brahmanandam (Proceedings on Engineering Sciences)
A new 39.9 MHz meteor radar was implemented in 2022 in Jhongli area, Taiwan, which is operated by National Central University in Taiwan and referred to as Chung-Li meteor radar. This radar is a bistatic radar with transmitter and receiver systems located at Bade City and Xinwu District, respectively, with a horizontal separation of about 22.3 km between them. The antenna array of the receiving system is composed of 5 cross-Yagi antenna elements for receiving circularly polarized radar returns from the meteor between different antenna pairs. In this article, detailed characteristics of the new Chung-Li VHF meteor radar will be introduced and the preliminary results of the meteor winds in height range from 80-110 km, which are estimated from the Doppler velocities of the echoes from under dense meteor trails, are presented. We find that the phases of observed meteor winds are in good agreement with those of Horizontal Wind Model (HWM). However, there are discrepancies in horizontal wind velocities between Chung-Li meteor radar observations and HWM model predictions. Plausible causes of the discrepancy are discussed.